THE EMERGING ROLE OF TIRZEPATIDE IN THE MANAGEMENT OF OBSTRUCTIVE SLEEP APNEA - Crüz, Kelson Palhari; Cabral, Isabela Rodrigues; Ferreira, Karolinne Nascimento; Viegas, Thiago de Oliveira Costa; Mauriz, Thayse Carvalho; Jardim, Laura Jullya de Oliveira; Lourenço, Mariana Penna Coelho; Sposito, Raffaella Azevedo; Iaremchuc, Katherine; dos Anjos, Natassiia Felsky Rodrigues; Almeida, Ana Laura Carvalho (Editora Impacto Científico, 2025)
Obstructive sleep apnea (OSA), common in individuals with obesity, causes respiratory interruptions during sleep and is associated with several comorbidities. Although CPAP is effective, low adherence limits its results. Tirzepatide, a dual GIP and GLP-1 agonist, has shown promise in the treatment of OSA by significantly reducing the apnea-hypopnea index, improving sleep quality, and promoting weight loss. This study aims to review the scientific literature to analyze the effectiveness of tirzepatide in obstructive sleep apnea, based on 13 recent articles selected through rigorous analysis. Current studies highlight tirzepatide’s superiority over other pharmacological therapies, with additional benefits in metabolic control and outcomes comparable to bariatric surgery. Therefore, based on current evidence, tirzepatide emerges as an effective and innovative alternative in the management of OSA. DOI: https://doi.org/10.56238/edimpacto2025.060-021